Editorial: seeing the light at the end of gastroscope ‐ complications after elective procedures are ready for NICE, bright decision aid tools ‐ authors' reply. Issue 1 (10th June 2022) - West, Joe; Card, Timothy R.; Crooks, Colin J.
LINKED CONTENT: This article is linked to Crooks et al papers. To view these articles, visit https://doi.org/10.1111/apt.16946 and https://doi.org/10.1111/apt.16961